Evaluation de L’effet insecticide de l’extrait méthanoique et les huiles essentielles des feuilles de Calamintha nepeta vis-à-vis des puceronsdes agrumes - BESSEDIK, ZINA; BAHRI, Bakhta (My University, 2018)
Among citrus-infested insects, aphids occupy a very special place as they are considered today among the most important insect pests inducing significant economic losses. From a perspective of seeking new auxiliaries likely to be used in biological control against these pests. This work focused on the evaluation of the bio-insecticidal efficacy of the methanoic extract and the essential oil of the leaves and stems of Calamintha nepeta on adults of the aphid species, Aphis spiraecola ,. The results obtained show that both extracts demonstrated a proven insecticidal action against citrus aphid species with a more marked efficacy of the essential oil with an LD50 of 0.08%. Similarly, the methanoic extract was very efficient with an LD50 of 2%. The remarkable insecticidal action of both extracts encourages the use of species as a source of bioactive natural compounds.
Keywords: Calamintha nepeta L; Essential oil; methanoic extract; insecticidal activity; LD50; huile essentielle; extrait méthanoïque; activité insecticide; كالمینتا نبییتا (النابتا; زیت اساسي; مستخلص میثانوییك; نشاط مبید للحشرات